Pengaruh Photovoice Interactive terhadap Peningkatan Pengetahuan Penanganan Bencana Longsor pada Remaja - Evi Supriatun; Uswatun Insani; Ariani Indrastuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study is to determine the effect of interactive photovoice on landslide disaster management knowledge in adolescents. This study uses a quasi experimental pre test and post test. T test results showed an increase in knowledge of landslide disaster management in adolescents compared with the control group (p value = 0,000). In conclusion, Photovoice interactive influences the knowledge of landslide disaster management in adolescent age groups in Salem District, Brebes Regency. Keywords: Landslide Disaster, Photovoice Interactive, Youth